Effectiveness Of Utilization Of Gutter Fund-Based Bos Funds At Public Elementary School 2 Budiasih - Eneng Eva Sundari; Risbon Sianturi; Sophia Choirotul Husniyyah; Dian Sudiana; Nisa UI (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2023)
Finances in an educational unit must be properly managed. It is important to participate in contributing to school funds so that the funds received function effectively and efficiently. The use of BOS or funds needs to be based on agreements and conclusions with the managers of these BOS funds, teachers and school institutions. Based on the results of the agreement, it is submitted in the form of written minutes of the meeting and signed by all meeting participants. This research is a type of qualitative method which requires the design of field case study research with descriptive-analytic characteristics. In collecting data using techniques for collecting this data will use, by way of interviews, documentation and observation. This can be shown by the results of this study by showing that the frequent delays in the allocation of funds at SD Negeri 2 Budiasih have an impact on learning activities at the school. If there is a delay in the distribution of school operational funds, the school's needs will become more difficult. Evaluation must be carried out so that school operational assistance funds are distributed on time with the right calculation in achieving all school activities and needs